Case Report: Familial Hypocalciuric Hypercalcaemia and Hashimoto's Thyroiditis - Mobarak, Shahd; Tarazi, Munir; Spiers, Harry; Santhakumar, Anjali; Forgacs, Bence (Frontiers in Surgery, 2020)
Introduction: Hypercalcaemia can be caused by many disorders. Primary hyperparathyroidism is the leading cause with parathyroidectomy being the definitive management. Familial hypocalciuric hypercalcaemia is a rarer cause in which resection of the parathyroid tissue does not result in normalised serum calcium. Case presentation: We report the unusual case of a 53-year-old lady who presented with hypercalcaemia and elevated parathyroid hormone with a presumed diagnosis of primary hyperparathyroidism. She remained hypercalcaemic after parathyroidectomy and was later diagnosed with familial hypocalciuric hypercalcaemia. During the first operation, a lymph node was also removed, and the histopathology report suggested a metastasis of follicular variant papillary thyroid carcinoma (FVPTC). After MDT discussion, the patient underwent a second exploration where total thyroidectomy and removal of the other parathyroid glands were performed. Hypercalcaemia completely resolved on surgical resection of the thyroid and parathyroid tissue, however histopathology revealed normal parathyroid glands and florid Hashimoto's thyroiditis. The initial diagnosis of FVPTC in the lymph node was revisited and the final histopathology report suggested an accessory thyroid nodule with florid Hashimoto's thyroiditis mimicking a lymph node. Conclusion: Our case demonstrates the diagnostic dilemma in hypercalcaemia that may lead a patient to undergo unnecessary invasive procedures; the misdiagnosis of FVPTC after the first operation resulted in a second more extensive procedure. Patients with no clear surgical target and urine CCCR in the grey/non-diagnostic area should be routinely offered genetic testing despite negative family history.